Gating by Cyclic Gmp and Voltage in the α Subunit of the Cyclic Gmp–Gated Channel from Rod Photoreceptors - Benndorf, Klaus (The Rockefeller University Press, 1999)
Gating by cGMP and voltage of the α subunit of the cGMP-gated channel from rod photoreceptor was examined with a patch-clamp technique. The channels were expressed in Xenopus oocytes. At low [cGMP] (<20 μM), the current displayed strong outward rectification. At low and high (700 μM) [cGMP], the channel activity was dominated by only one conductance level. Therefore, the outward rectification at low [cGMP] results solely from an increase in the open probability, P (o). Kinetic analysis of single-channel openings revealed two exponential distributions. At low [cGMP], the larger P (o) at positive voltages with respect to negative voltages is caused by an increased frequency of openings in both components of the open-time distribution. In macroscopic currents, depolarizing voltage steps, starting from −100 mV, generated a time-dependent current that increased with the step size (activation). At low [cGMP] (20 μM), the degree of activation was large and the time course was slow, whereas at saturating [cGMP] (7 mM) the respective changes were small and fast. The dose–response relation at −100 mV was shifted to the right and saturated at significantly lower P (o) values with respect to that at +100 mV (0.77 vs. 0.96). P (o) was determined as function of the [cGMP] (at +100 and −100 mV) and voltage (at 20, 70, and 700 μM, and 7 mM cGMP). Both relations could be fitted with an allosteric state model consisting of four independent cGMP-binding reactions and one voltage-dependent allosteric opening reaction. At saturating [cGMP] (7 mM), the activation time course was monoexponential, which allowed us to determine the individual rate constants for the allosteric reaction. For the rapid rate constants of cGMP binding and unbinding, lower limits are determined. It is concluded that an allosteric model consisting of four independent cGMP-binding reactions and one voltage-dependent allosteric reaction, describes the cGMP- and voltage-dependent gating of cGMP-gated channels adequately.